A modern guide to rethinking economics - Rochon, Louis-Philippe; Rossi, Sergio, 1967- (Cheltenham, UK : Edward Elgar Publishing, 2017)
This book addresses the urgent need to rethink economics by providing readers at all levels with thoughtful chapters on a range of relevant economic topics.
Contents:Introduction Louis-Philippe Rochon and Sergio RossiPART I CONCEPTUAL AND METHODOLOGICAL ISSUES1. Rethinking the foundations of macroeconomics Claude Gnos2. Rethinking the economic role of the State Hassan Bougrine3. Rethinking economics for a pluralist approachGuillaume Vallet4. Rethinking uncertaintyRod O'Donnell 5. Rethinking exchange and pricesJean-Luc Bailly6. Rethinking money Jean-Francois Ponsot7. Rethinking economic growth Angel AsensioPART II ECONOMIC POLICY ISSUES8. Rethinking income distribution Omar F. Hamouda9. Rethinking fiscal policy Matthieu Llorca10. Rethinking the role of banks Virginie Monvoisin11. Rethinking monetary policy Louis-Philippe Rochon12. Rethinking monetary and financial stabilityFaruk UElgen13. Rethinking development Esteban Perez Caldentey14. Rethinking health economics Robert McMasterPART III GLOBAL ISSUES15. Rethinking international tradeRudiger von Arnim16. Rethinking the international monetary and financial architecture Sergio Rossi17. Rethinking the environment Robert H. Scott18. Rethinking energy Lynne Chester19. Rethinking politics Stephen Parsons20. Rethinking social security Spartaco Greppi21. Rethinking antipoverty policy Steven PressmanIndex
Includes bibliographical references and indexes.
Keywords: Economics